Effects of Ban Xia Xie Xin Decoction on GERD of Cold and Heat in Complexity Syndrome - Tandean, Erick Okto; Sumantri, Twinky Zebrina Cysta; He, Ling; Amalia, Anindini Winda (Universitas Muhammadiyah Sumatera Utara, 2026)
Abstract: Gastroesophageal Reflux Disease (GERD) presents significant diagnostic challenges and diminishes quality of life. This study evaluates the efficacy of Ban Xia Xie Xin Decoction on patients with GERD exhibiting